PERBEDAAN PARADIGMA EKONOMI KONVENSIONAL DAN EKONOMI ISLAM DALAM TEORI DAN REALITA (Perspektif Mikro) (Islamic Economics and Business Faculty of UIN Antasari, 2012)
Conventional economy is different from Islamic economy. The former is based on thebehavior of economic units that is not tied to certain Sharia norms. On the contrary, the latterasserts that individual behavior is limited to Sharia rules. In practice, conventional economy onlypays attentions to changes taking place in economic variables. In contrast, not only does Islamiceconomy focuses on the changes, it also avoids what Sharia forbids. The behavior of Islamiceconomy actors is based on the theory of Islamic economy (consisting of such concepts as tauhid,adl, nubuwah, khilafah dan maad), and its principles: ownership, freedom and social justice. In prac-ticing these, the actors of Islamic economy are guided by ethics. Rules like these are not to befound in conventional economy, in which rentseeking can distort economic pratices which maylead to business failures and economic unstability.